ANALYSIS OF EFFECT OF SERVICES TO CUSTOMER SATISFACTION IN HOTEL MS IN SANGATTA - Karya, Karya (EKONOMIA, 2013)
The purpose of this study to determine the level of customer satisfaction in terms of service include reliability, responsiveness, empathy, assurance and real form provided by the Hotel MS in Sangatta.Penelitian held for 3 Months ( April to June 2013 ) at the Hotel MS in Sangatta,  with service to customer satisfaction in hotels MS in Sangatta. research conducted : The study of literature, field observations, interviews, documentation, file collection and analisis. File that  in the research include : an overview of the cooperative, and the organizational structure of the respondents' answers. analysis of file using multiple regression analysis with formula Y = a + b1X1 + b2X2 + b3X3 + b4X4 b5X5 + e.            The results obtained by the calculation of regression equation as follows : Y = 0.711 + 0.121X1 + 0.136X2 + 0.132X3 + 0.163X4 + 0.173X5From these equations can be explained that each coefficient b obtained a positive value, it means if each variable studied further enhanced, then together will affect customer satisfaction. If the variable reliability (X1) increased one percent, then increased 0,121 % customer satisfaction. If the response variable (X2) increased one percent, then increased 0.136 % customer satisfaction. If empathy variables (X3) increased one percent, then increased 0.132 % customer satisfaction . If the collateral variable (X4) increased one percent, then increased 0.163 % customer satisfaction. If the real form of the variable (X5) increased one percent, then increased 0.173 % customer satisfaction.